Effect of post-harvest starvation and rinsing on the microbial numbers and the bacterial community composition of mealworm larvae (Tenebrio molitor). (August 2017) - Wynants, E.; Crauwels, S.; Lievens, B.; Luca, S.; Claes, J.; Borremans, A.; Bruyninckx, L.; Van Campenhout, L.
Abstract: Specific processing steps after industrial rearing of insects for food and feed, being starvation and rinsing, are assumed to have an impact on their microbial quality. The aim of this study was to assess the effect on the microbiota of starvation (24 or 48 h, 10 or 30 °C) and rinsing (1 min using tap water) at the end of the rearing period of yellow mealworm larvae ( Tenebrio molitor ). Microbial numbers were determined using plate counts and the microbial community composition using metagenetic analyses. Total viable counts ranged from 7.7 to 8.4 log cfu/g for all treatments. Starvation did not evoke prominent shifts in the bacterial community, which was predominated by Proteobacteria and Firmicutes. No bacterial food pathogens were detected using metagenetics. Our data suggest that the processing steps under study do not contribute to a better microbial quality of fresh mealworm larvae. Industrial relevance: As insects and insect-based foods are receiving more attention and are already being marketed in some European countries, more insects farms are being established. Rearing companies often optimise their practices by trial and error and no general hygiene codes are available. According to the Netherlands Food and Consumer Product Safety Authority (2014), mealworm larvae are generally starved and rinsed after rearing to empty their gut, but the impact of these practices has not been investigated so far. Hence, the necessity for rearers to incorporate these steps in their rearing procedures has not been demonstrated. The Belgian SHC (Superior Health Council) and FASFC (Federal Agency for the Safety of the Food Chain) have recommended in their advice (2014) to investigate these steps. In addition, as edible insects will be defined as novel foods as from 1 January 2018 according to the European Novel Food Regulation (EU) No. 2015/2283, more information is needed on their safety, which is related to production hygiene. Highlights: Mealworm larvae were starved (24/48 h, 10/30 °C) and rinsed (1 min, tap water). Total viable counts ranged from 7.7 to 8.4 log cfu/g for all treatments. Neither starvation nor rinsing of mealworms after rearing reduced microbial numbers. The bacterial community was dominated by the phyla Proteobacteria and Firmicutes. Starvation did not consistently change the bacterial community composition.